2020
DOI: 10.1021/acs.energyfuels.0c03732
|View full text |Cite
|
Sign up to set email alerts
|

Cu/CuMgAlOx-Catalyzed Guaiacol Hydrodeoxygenation in Supercritical Methanol: A Modeling Mechanistic Insight for Lignin-Derivatives Upgrading

Abstract: The development of an economic and sustainable catalytic system was crucial for lignin-based biorefinery. Herein, we reported a low-cost Cu/CuMgAlO x catalyst with promising activity toward lignin hydrodeoxygenation (HDO) through a H2-free method. Supercritical methanol was used as the hydrogen donor, solvent, and reactant simultaneously. Guaiacol was employed as a representative lignin model compound to reveal the HDO mechanism of lignin derivatives. HDOs of guaiacol performed at 250, 275, 300, and 350 °C wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…The catalytic performances of the catalysts were initially evaluated by guaiacol HDO in supercritical methanol as a model reaction. It has been indicated that guaiacol undergoes an initial HDO–hydrogenation–deep HDO procedure to produce cyclohexanes, where the deep HDO of cyclohexanols is the rate-limiting step and is mainly controlled by the catalyst acidity. Therefore, the facilitation toward the HDO of cyclohexanols to cyclohexanes by the SA modification was focused.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The catalytic performances of the catalysts were initially evaluated by guaiacol HDO in supercritical methanol as a model reaction. It has been indicated that guaiacol undergoes an initial HDO–hydrogenation–deep HDO procedure to produce cyclohexanes, where the deep HDO of cyclohexanols is the rate-limiting step and is mainly controlled by the catalyst acidity. Therefore, the facilitation toward the HDO of cyclohexanols to cyclohexanes by the SA modification was focused.…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the total yields of monomers as well as yields of cyclohexanols and cyclohexanes resulting from guaiacol HDO with the SA-Cu/CuMgAlO x catalysts as a function of SA dosage. The reactions were performed at 300 °C for 2 h to give certain yields of cyclohexanes as the activity indicator . The detailed product distributions were given in Table S1 as a reference.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations